THE EFFECTS OF MTBE BLENDING ON V/L RATIO OF INDONESIAN PREMIUM GASOLINE - E. Jasjfi; Rasdinal Ibrahim (Scientific Contributions Oil and Gas, 1989)
In preparation for possible future scarcity of lead alkylate as well as due to environmental consideration in the country, studies are being conducted in Indonesia on the late of Oxygenated Organic compounds as octane boosting components. Methyl ter-butyl ether (MTBE) has received a great deal of attention on account of its relatively better characteristic in comparison with other oxygenates.            Since the use of MTBE affects the front-end volatility of gasoline, it is decmed interesting to present in this paper the results of a study on the effects of this compound on the vapour-liquid ratio of typical Indonesian premium gasoline. Although V/L ratio has not been an item in Indonesia gasoline specification, it is nevertheless a good measure of the vapour lock tendency of the fuel.